Multi-tier application programming with PHP : practical guide for architects and programmers - Wall, David, 1974- (Morgan Kaufmann practical guides series., 2004)
Some of the benefits of using PHP is that it is easier to learn and cheaper than using Java J2EE Enterprise or .NET platforms. In concert with a database server and a client-side scripting language like Javascript, PHP can be made to do n-tier application work which is a way of designing applications for ease of maintenance and modification, as well as better performance under load. PHP has been steadily gaining ground in web application development over Perl during the last 2 years and while there are resources for learning PHP, there is virtually nothing that covers the n-tier application as.